Emergency Obstetric Protocol and its Effect on Practices of Interns Nursing Students (Medico Legal Update, 2021)
Background: obstetric emergencies are life threatening medical condition that occurs during pregnancy,labor, or the postpartum period.Moreover, internships offer carefully planned, monitored work experiencewhich allow the opportunity to apply knowledge and skills in a professional setting.Study Aim: to evaluate the effect of emergency obstetric protocol on the practices of interns nursing students.Methodology: A quasi experimental studyconducted in technical institute of nursing faculty of nursing andin emergency department, intensive care unit and labor unit of maternity hospital Ain- Shams University.A convenient sample of one hundred of all female interns nursing studentsin the technical institute ofnursing faculty of nursing Ain- Shams University from period (October 2019 to March 2020). Tools ofdatacollection:Obstetric triage observational checklistusedfor assessment of intern nurses’ practices related totriage of obstetric emergencies casesandobservational checklists toolforassessment of intern nurses’ practicesrelated nursing managementof common obstetrics emergencies pre and post protocol implementation.Results: Showed statistically significant improvements in intern nurses’ practical skills related to triageprocess and nursing care of common obstetric emergencies immediately post interventionand in follow upphase.Conclusion: Implementing emergency obstetric protocol had a positive effect on the practices of internsnursing students.